DNA polymorphism of Pythium eight species of causing tomato seedlings damping-off disease in Hangzhou region - LOU Bing-gan; ZHANG Bing-Xin; ZHANG Yao-zhou (浙江大学学报. 农业与生命科学版)
Twenty-five random primers screened from 28 were ultilized for Random Amplified Polymorphic DNA (RAPD) analysis of 10 isolates covered 8 species of Pythium. The result showed that DNA polymorphism of Pythium was abundant. The Nei's genetic distance of 10 isolates of Pythium was initially calculated. It was used to generate unweighted pair-group method using arithmetic averages (UPGMA) dendrogram to show genetic relationship among the ten isolates in 8 species of Pythium. The results showed that the nearest genetic relationship were between P. kunmingense and P. irregulare, between P. aphani-dermatum and P. tardicrescens, and between P. ultimum and P. debaryanum. The UPGMA dendrogram showed the eight species of Pythium were classified into three groups. The first group was P. kunmingense, P. irregulare and P. spinosum, the second group was P. aphanidermatum and P. tardicrescens, and the third group was P. ultimum, P. dissotocum and P. debaryanum.